Mono, Di and Trifunctional Cyclic Organic Peroxides: The Effect of Substituents and Ring Size on their Thermolysis in 1,4-dioxan - Nesprias, Rosa Karina (2013)
The thermal decomposition reaction of cyclic organic peroxides was studied in 1,4-dioxan at initial concentrations between ~10–4 and 10–2 mol L–1 and at a temperature interval between 100 and 170°C, according to the thermal stability of each compound. The kinetic behaviour observed in all systems studied follows a pseudo first order kinetic law up to at least ~86 % of peroxide conversion. An important substituent effect is operative on the rate constant values and consequently on the activation parameters of the thermal decomposition reaction. The application of different treatments (compensation affect or a statistical treatment) on the kinetic data shows the existence of two sets of cyclic peroxides with comparable kinetic behaviour. Different peroxide–solvent interaction mechanisms can be considered within each series.